DEVELOPING MATHEMATICAL COMPETENCE THROUGH ARTIFICIAL INTELLIGENCE TECHNOLOGIES (International journal of artificial intelligence, 2026)
This article analyses the application of artificial intelligence technologies in developing the mathematical competence of higher education students. The didactic affordances of adaptive learning platforms, intelligent tutoring systems and generative artificial intelligence tools are examined, and their effectiveness is substantiated through statistical methods on the basis of the results of a pedagogical experiment.